1969
DOI: 10.1099/00222615-2-2-81
|View full text |Cite
|
Sign up to set email alerts
|

Composition Of Cell Walls Of Clostridium Sordellii And Clostridium BiferMentans And Its Relation To Taxonomy

Abstract: A N S (Tissier and Martelly, 1902) and CZ. sordellii (Sordelli, 1922; Hall and Scott, 1927) are in many respects similar organisms. Clark and Hall (1937) found that they are morphologically and culturally indistinguishable and serologically related-only the non-pathogenicity of the first and high pathogenicity of the second distinguish them. Stewart (1938), after investigation of some few strains, suggested that CZ. sordeZZii is a pathogenic variant of CZ. bifermentans and that they should be regarded as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1970
1970
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
4
1
Order By: Relevance
“…On the other hand, the peptidoglycans obtained from C. histolyticum and C. bifermentans were composed of glutamic acid, alanine and DAP in the molar ratio of approximately 1:1.5:1, indicating that the peptidoglycans of these organisms differ from those of C. botulinum in the molar ratio of alanine to glutamic acid. Novotonr [12] reported that the cell wall preparations of C. bifermentans contained both DAP and lysine, but we could not detect lysine except DAP in the peptidoglycan of the organism. As was reviewed by Schleifer and Kandler [16], there are no bacterial peptidoglycans containing both DAP and lysine as the primary amino acids.…”
Section: Chemical Composition and Antigenic Properties Ofcontrasting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, the peptidoglycans obtained from C. histolyticum and C. bifermentans were composed of glutamic acid, alanine and DAP in the molar ratio of approximately 1:1.5:1, indicating that the peptidoglycans of these organisms differ from those of C. botulinum in the molar ratio of alanine to glutamic acid. Novotonr [12] reported that the cell wall preparations of C. bifermentans contained both DAP and lysine, but we could not detect lysine except DAP in the peptidoglycan of the organism. As was reviewed by Schleifer and Kandler [16], there are no bacterial peptidoglycans containing both DAP and lysine as the primary amino acids.…”
Section: Chemical Composition and Antigenic Properties Ofcontrasting
confidence: 82%
“…The chemical constituents of the cell walls of various species of the genus Clostridium were qualitatively determined by Cummins and colleague [2,3] and these results were used for classification of this genus [19]. Although there are a few studies on the quantitative chemical analyses of peptidoglycans of some clostridia [12,13,15], there are no reports on various types of Clostridium botulinum, except type A [21]. Our previous studies [24] on the cell walls of C. botulinum type A have shown that the peptidoglycan is of the directly cross-linked diaminopimelic acid (DAP)-containing type in which the cross-linkage of peptide moiety extends from the r-amino group of DAP of one peptide to the carboxyl group of D-alanine of another adjacent peptide subunit.…”
mentioning
confidence: 99%
“…Clostridium sp. reportedly have urease activity [40]. A study conducted by Crociani et al [41] of urease activity in the stomach (fundus and antrum), content, and soft rabbit feces showed that Clostridium sp.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we speculated that these particles were synthesized intracellularly and released through spontaneous cell rupture after cell wall degradation, similar to the secretion of toxins A and B from Clostridium difficile 49 . To verify this hypothesis, a hypertonic solution was used to block bacterial autolysis 50 . Expectedly, numerous particles with a diverse range of sizes were observed inside the protoplast of RJ-1 (Fig.…”
Section: Rj-1 Mediated Synthesis Of Inps and Induction Of Ferroptosis...mentioning
confidence: 99%